Analisis Terhadap Ganti Kerugian Akibat Wanprestasi Dalam Perjanjian Utang Piutang (Studi Kasus Putusan Nomor 59/Pdt.G/2022/PN Mkd) - Tsania Nurul Azkia; Arief Suryono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Humans are essentially social creatures who need help from other people in meeting their daily needs, especially those related to economic problems. The economy is fundamentally related to agreements, as these agreements are created to ensure that both parties comply with and fulfill their obligations. However, in fact, currently there are still many default disputes due to debtor negligence so that the legal consequences are cancellation of previously agreed agreements, transfer of risk, as well as compensation for costs, losses and interest. Apart from that, resolving default disputes can also be done by filing a lawsuit by creditors in district court as in case number 59/Pdt.G/2022/PN Mkd. After going through considerations, the case was decided by the judge and granted in part because there was one of the arguments of the lawsuit which was not in accordance with positive law in Indonesia.